Clinical implications of pulmonary nodules detected in children. Issue 1 (19th November 2020) - Barber, Andrew; Passarelli, Patrick; Dworsky, Zephyr D.; Gatcliffe, Chelsea; Ryu, Julie; Lesser, Daniel J.
Abstract: Introduction: The management of children found to have pulmonary nodules is not well established. We determined how often diagnostic testing was pursued, the outcome of diagnostic testing, and how often pulmonary nodules were given a definitive diagnosis. Method: A retrospective review of patients found to have pulmonary nodules. Patients with oncologic diagnoses were excluded. Data collected included number of nodules, presence of pre‐existing systemic disease, laboratory testing, presence of respiratory symptoms, repeat imaging, biopsy result, and final diagnosis. Results: We identified 88 patients, of which 56 (64%) had a single nodule, 21 (24%) had a pre‐existing nononcologic systemic disease, and four patients (5%) had a new systemic disease identified at the same time the nodule(s) was found. In otherwise healthy patients presenting with a solitary nodule, 94% did not have a definitive diagnosis and none went on to be diagnosed with systemic disease. Serum infectious work‐up result for tuberculosis, coccidioidomycosis, histoplasmosis, or aspergillosis was not significantly different between single and multiple nodule/systemic illness groups. No previously healthy patients presenting with a solitary nodule were later diagnosed with malignancy. Conclusion: Diagnostic workup for a solitary pulmonary nodule was often inconclusive, especially if the patient did not have symptoms at presentation. Pulmonary nodules were not the sole presenting sign of systemic disease for any subjects. We suggest that in an otherwise healthy pediatric patient found to have an asymptomatic single pulmonary nodule, observation without laboratory work‐up or repeat imaging is a reasonable option.